Hematological and Biochemical Parameters in Female Black King Fish Cobia (Rachycentron canadum) - Prem Kumar; S. Elangeswaran; A.R. Thirunavukkarasu; M. Kailasam; M. Saiyad Musthafa; R. Subburaj; G. Thiagarajan (Fishery Technology, 2023)
Black King Fish Cobia (Rachycentron canadum) is a potential candidate fish for aquaculture. In the present investigation an attempt was made to understand the biochemical and hematological parameters in different stages of maturity in females. Blood samples were collected from different stages of maturity and subjected to hematological parameters such as hemoglobin (Hb), Total Erythrocyte Counts (RBC), Total Leucocytes Count (WBC) and hematocrite value (Ht) and biochemical parameters such as blood glucose, total serum protein, cholesterol and triglycerides. The hemoglobin level was 15.77 ± 0.15 gm/dl in immature female, 14.57 ± 0.92 gm/dl in matured female and 11.63 ± 0.12 gm/dl in spent fish. The hematocrite value also show similar trend with 46.6 ± 1.15, 45.34 ± 3.45 and 34.67 ± 0.58 in immature, mature and spent fish respectively. The total RBC count was 5.40 ± 0.1 ml/ cm3 in immature, 5.2 ± 0.24 ml/cm3 in mature and 3.83 ± 0.12 ml/cm3 in spent fish. The WBC count also showed a similar trend of 16.30 ± 0.1 cells/mm3, 15.83 ± 0.34 cells/mm3 and 11.57 ± 0.12 cells/mm3 in immature, mature and spent fish respectively. Significant change was observed in the blood glucose level in all the stages of maturity. The serum cholesterol level was significantly higher in mature fish (291.67 ± 1.00 mg/dl) than immature (204.0 ± 0.89 mg/dl) and spent (203.67 ± 1.0 mg/dl) fish. The results of the present investigations indicated higher metabolic activity in immature fish than matured and spent fishes and also indicated gradual mobilization of vital blood parameters during the process of maturation.